Чурыт пус: кылбуръёс / Сергей Матвеев - Матвеев Сергей Васильевич (Удмуртия, 1999)
Экземпляры: ф.18 (2001) / Инвентарный номер: 43157 / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: М 33 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5